2014
DOI: 10.1016/j.ultsonch.2013.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound assisted synthesis of {[Cu2(BDC)2(dabco)].2DMF.2H2O} nanostructures in the presence of modulator; new precursor to prepare nano copper oxides

Abstract: As a new precursor to prepare nano copper oxide, nanostructures of porous metal organic framework (MOF) {[Cu2(BDC)2(dabco)].2DMF.2H2O} (1) have been synthesized in the presence of acetic acid as a modulator via sonochemical method. Different concentrations of metal ion, organic linkers, modulator reagent and also different sonication times were held to improve the quality of nanostructures. Ultrasound irradiation helps nucleation step of the oriented attachment of modulation method and nanoparticles with a few… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 43 publications
3
12
0
Order By: Relevance
“…Another MOF {[Cu 2 (BDC) 2 (dabco)] 2DMF 2H 2 O was obtained by varying reactant concentrations and sonication times in the presence of acetic acid as a modulator [54]. It was found that when reactants are sonicated for about 90 minutes, it led to larger particles without agglomeration.…”
Section: Sonochemical Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Another MOF {[Cu 2 (BDC) 2 (dabco)] 2DMF 2H 2 O was obtained by varying reactant concentrations and sonication times in the presence of acetic acid as a modulator [54]. It was found that when reactants are sonicated for about 90 minutes, it led to larger particles without agglomeration.…”
Section: Sonochemical Synthesismentioning
confidence: 99%
“…Various concentrations of modulator were also used during synthesis to reduce interactions between metal ions and organic ligands, therefore potentially providing control over the crystal growth. For example, at higher concentration of modulator one-dimensional growth was observed resulting in nanorods [54].…”
Section: Sonochemical Synthesismentioning
confidence: 99%
“…Acetic acid has the same chemical functionality as the organic linkers, so it can alter the equilibrium between the organic linkers and metal ions and inhibit the coordination interaction between them, thus controlling the synthesis of Cu‐BTC. Modulator reagent has a regulatory effect on the rate of crystal growth and framework extension, which has effects on the morphology and size of samples . Reaction conditions and results from synthesized Cu‐BTC were listed in Table .…”
Section: Resultsmentioning
confidence: 99%
“…al. (499 m 2 /g) . The mesoporousity of the catalyst was demonstrated by N 2 adsorption–desorption diagrams and hysteric loop from BJH desorption dV/dlog(D) pore volume diagram shown in Figure .…”
Section: Resultsmentioning
confidence: 99%